2000
DOI: 10.1046/j.1365-294x.2000.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographical pattern correlates with Pliocene mountain building in the alpine scree weta (Orthoptera, Anostostomatidae)

Abstract: Most research on the biological effects of Pleistocene glaciation and refugia has been undertaken in the northern hemisphere and focuses on lowland taxa. Using single-strand conformation polymorphism (SSCP) analysis and sequencing of mitochondrial cytochrome oxidase I, we explored the intraspecific phylogeography of a flightless orthopteran (the alpine scree weta, Deinacrida connectens) that is adapted to the alpine zone of South Island, New Zealand. We found that several mountain ranges and regions had their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
132
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(145 citation statements)
references
References 53 publications
11
132
2
Order By: Relevance
“…E. ephippiger shows characteristic signs of repeated and recent range changes, for example, the complex, non-concordant clines in different traits (Oudman et al, 1989(Oudman et al, , 1990Duijm, 1990;Ritchie et al, 2001). The only similar results we can find are those of Trewick et al (2000), who found mtDNA differences of a similar magnitude between populations of the alpine scree weta, another flightless orthopteran, confirming that isolation which predates Pleistocene glaciations can result in extensive intraspecific divergence without speciation. However, the reasons for the lack of greater divergence in other traits remain curious.…”
Section: Genetic Divergence Between Lineagessupporting
confidence: 60%
“…E. ephippiger shows characteristic signs of repeated and recent range changes, for example, the complex, non-concordant clines in different traits (Oudman et al, 1989(Oudman et al, , 1990Duijm, 1990;Ritchie et al, 2001). The only similar results we can find are those of Trewick et al (2000), who found mtDNA differences of a similar magnitude between populations of the alpine scree weta, another flightless orthopteran, confirming that isolation which predates Pleistocene glaciations can result in extensive intraspecific divergence without speciation. However, the reasons for the lack of greater divergence in other traits remain curious.…”
Section: Genetic Divergence Between Lineagessupporting
confidence: 60%
“…The Pliocene saw the uplift of most of the major mountains seen in New Zealand today, including the Southern Alps, and the Pleistocene was a period of cycling glacial and interglacial stages. Together, these events drove diversification in many terrestrial invertebrate groups (Trewick et al, 2000;Morgan-Richards et al, 2001;Trewick, 2001;Buckley & Simon, 2007). Such diversification should render a clear phylogenetic pattern of reciprocal monophyly of both the New Zealand clades and their sister taxa.…”
Section: Introductionmentioning
confidence: 99%
“…The constancy in tree topology across the different methods of analysis together with the high posterior probabilities and bootstrap support values confirms the validity of the two COI gene lineages recovered. Although variation within other anostostomatid species seems to vary considerably, with values of up to 7.6% sequence divergence being reported (Trewick et al 2000), investigation of past gene flow between the two specified populations supports historical isolation and diversification. Morphometrically-distinguishing characters between the north-western and eastern populations as revealed by canonical variates (discriminant) analysis (CVA) (Table 2) include: pronotum length (C1), head width (C5), mandible length (C7), front leg femur width (C13), front tibia length (17), front tibia width (C18), tusk base thickness (C21) and tusk length (C22) for the male data, and pronotum length (C1), eye length (C3), hind femur length (C14), and hind femur width (C15) for females.…”
Section: Discussionmentioning
confidence: 95%